Belminus corredori, a new species of Bolboderini (Hemiptera: Reduviidae: Triatominae) from Santander, Colombia - Galvão, Cleber; Angulo, Victor M. (Zootaxa, 2006)
Belminus corredori, a new species of Bolboderini, is described on the basis of specimens collected in Puente Tierra, municipality of San Gil, Departament of Santander, Colombia. Specimens were found in well-built dwellings located approximately 1,810 meters of altitude in a region characterized by the presence of dry mountain forest.